The Concept of Ta’abbudi and Ta’aqquli in Islamic Law - Ismail Keri (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2021)
The discourse on the concepts of ta'abbudi and ta'aqquli in Islamic law is a discourse that always lives and develops in tandem with the development of science. Understanding the concept of ta'abbudi and ta'aqquli should continue to use the rules, norms and arguments that serve as guidelines. The concept of ta'abbudi and ta'aqquli, it is urgent to get a basic conception, as a reference in formulating the relevant concept of Islamic law. This study is a conceptual study of literature with a normative theological approach. The findings in this study are that ta'abbudi is a textual provision (The Qur’an and hadith) in the field of worship that must be obeyed even though they do not know the rational reasons, while ta'aqquli allows there to be benefits according to rational reasons, so that reason is given space. The object is also different, ta'abbudi is focused on mahdah worship, while ta'aqquli is in the matter of muamalah. In addition, ta'abbbudi is static, does not provide opportunities for ijtihad, while ta'aqquli provides opportunities for ijtihad. In the construction of Islamic law in the application of the concepts of ta'abbudi and ta'aqquli it turns out to have two legal dimensions. This means that there are certain problems that require ta'abbudi and also conditions that require ta'aqquli. It is not focused on the meaning of lafadz, but rather on the implementation of the law. Because the form of benefit lies in the philosophical meaning of Allah's decree which will have implications for human actions.